2017
DOI: 10.29303/jpft.v2i4.305
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Hasil Belajar Fisika Melalui Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Berbantuan Kartu Soal dengan Model Pembelajaran Direct Instruction Di SMAN 7 Mataram Tahun Ajaran 2015/2016

Abstract: Abstract−This research is aimed to know the difference between physics learning result through numbered heads together type cooperative learning model helped by question card and physics learning result through direct instruction learning model at SMAN PENDAHULUANFisika adalah kumpulan pengetahuan, cara berfikir, dan penyelidikan. Fisika dipandang sebagai suatu proses dan sekaligus produk sehingga dalam pembelajarannya harus mempertimbangkan strategi atau metode pembelajaran yang efektif dan efisien.Pembelajar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Previous research results showed that the use of physics comics can foster students' reading interest and literacy in physics learning. The use of physics comics accompanied by student worksheets can train the skills of (Putri et al, 2018) the scientific process in students (Susanti et al, 2016). Comic learning media can improve learning outcomes and is practically used as teaching materials.…”
Section: 2%mentioning
confidence: 99%
“…Previous research results showed that the use of physics comics can foster students' reading interest and literacy in physics learning. The use of physics comics accompanied by student worksheets can train the skills of (Putri et al, 2018) the scientific process in students (Susanti et al, 2016). Comic learning media can improve learning outcomes and is practically used as teaching materials.…”
Section: 2%mentioning
confidence: 99%
“…Nilai tertinggi kelas eksperimen adalah 80 yang diperoleh oleh 3 siswa, sementara nilai tertinggi untuk kelas kontrol adalah 73,3 yang diraih oleh 2 orang siswa sebagaimana ditunjukkan pada Gambar 1. Gambaran nilai kelas ekperimen tersebut masih dibawa nilai pembelajaran TGT yang dilaporkan oleh (Susanti et al, 2016;Damayanti and Apriyanto, 2017;Rahmawati, 2017). Hal tersebut diakibatkan oleh kekurangan pada tahap 4 (turnamen) dari TGT berbasis kartu ini, yaitu siswa mencari jawaban yang tertulis pada kartu berdasarkan sola yang dibacakan oleh guru.…”
Section: ) Hasil Belajarunclassified